2013
DOI: 10.1113/expphysiol.2012.070359
|View full text |Cite
|
Sign up to set email alerts
|

Acute upper airway muscle and inspiratory flow responses to transcranial magnetic stimulation during sleep in apnoeic patients

Abstract: New Findings r What is the central question of this study?Peripheral hypoglossal nerve stimulation is a novel therapeutic approach aimed at recruiting lingual muscles electrically and thus relieving pharyngeal airflow obstruction during sleep but the effects of corticomotor stimulation of upper airway muscles during sleep are unknown. r What is the main finding and its importance?Using transcranial magnetic stimulation, we show that corticobulbar excitability of the submental muscles is decreased during sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 38 publications
2
26
2
Order By: Relevance
“…Accordingly, a recent paper [36] has shown that the activation of the cortical-bulbar pathway was reduced during NREM sleep in apneic patients, as demonstrated by increased MT and prolonged MEP latency recorded from the submentalis muscle. This diminished excitability is hypothesized to result from the combined effects of the thalamo-cortical system hyperpolarization and the modified reactivity to sensory inputs [37,38], leading to a prevailing tonic GABAergic and glycinergic inhibitory inputs to motor neurons [37], and thus probably resulting in a globally decreased excitability of the motor cortex and conductivity of the fastest conducting cortical-spinal projections.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, a recent paper [36] has shown that the activation of the cortical-bulbar pathway was reduced during NREM sleep in apneic patients, as demonstrated by increased MT and prolonged MEP latency recorded from the submentalis muscle. This diminished excitability is hypothesized to result from the combined effects of the thalamo-cortical system hyperpolarization and the modified reactivity to sensory inputs [37,38], leading to a prevailing tonic GABAergic and glycinergic inhibitory inputs to motor neurons [37], and thus probably resulting in a globally decreased excitability of the motor cortex and conductivity of the fastest conducting cortical-spinal projections.…”
Section: Discussionmentioning
confidence: 96%
“…, ; Melo‐Silva et al . a ). Transcranial magnetic stimulation‐induced twitches applied during sleep over the corticomotor somatotopic representation of the tongue on isolated breaths briefly recruit UA dilator muscles and improve the airflow dynamics of flow‐limited respiratory cycles without arousing OSA patients (Dempsey et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the study featured in this issue of Experimental Physiology (Melo‐Silva et al 2013), TMS was used to stimulate the somatotopic representation of the tongue in the motor cortex of sleeping patients with obstructive sleep apnoea (OSA) in order to stimulate contraction of upper airway muscles. Obstructive sleep apnoea is a very common condition, in which the contractions of the upper airway muscles, especially the tongue musculature, fail to stabilize or dilate the airway adequately during inspiration in sleep.…”
mentioning
confidence: 99%
“…The ‘route one’ approach of stimulating the hypoglossal nerve, the motor nerve to the tongue, has been used with some success, but this method requires surgery (Eastwood et al 2011). The investigation by Melo‐Silva et al (2013) shows that TMS can be used to cause activation of upper airway muscles and improve airflow and inspired volume during episodes of reduced airflow, and this is achieved without waking the patient. There was no effect on activation of chest wall/diaphragm muscles.…”
mentioning
confidence: 99%
See 1 more Smart Citation